Keanekaragaman Burung di Kampus Uin Raden Intan Lampung - Apriliano, Amanda; Anwar, Chairul; Pawhestri, Suci Wulan; Satiyarti, Rina Budi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2018)
Biodiversity of Indonesia is worldwide known. One of those is bird biodiversity. The native utilize birds as a pet. It is because birds have a beautiful color and voice. Therefore, Rare birds is likely to be hunted to get their aesthetic value. Raden intan Islamic ngy (UIN RIL) were a part of city forest. Trees and scrub were considered as bird habitat. The aim of this research is to identify birds in UINRIL campus, gruping the bird based on their exctinction.This research was done in five station each three times. The method is point count. All data were collected at 06.00-09.00 and 15.00-18.00 WIB. Data were analyzing using deskriptif quantitative approach. Diversity index (H’) for all station is 1.166-2.351. Diversity average at all station were(H’) 2,023. This research had success write 24 species of birds from 16 famili. Three of them were under government surveillance pp no. 7 year 1999. They are cekakak sungai (Todirhamphus chloris), madu sriganti (Nectarinia jugularis), and madu kelapa (Anthreptes malacensis).